DOI: 10.31274/etd-180810-2235
|View full text |Cite
|
Sign up to set email alerts
|

Framing Chinese migrant workers: A comparison of media coverage in Mainland China and Hong Kong

Abstract: This study investigates the framing of Chinese migrant workers in articles published in two Mainland Chinese newspapers and two Hong Kong newspapers from 2004 to 2009. The content analysis reveals significant differences in the news frames between the two regions. Attribution of responsibility and morality are the most frequently used frames in Mainland newspapers, while human interest and responsibility frames dominate coverage in Hong Kong newspapers. Government officials are the most popular sources cited b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…News media has an intimate bond with framing, which is expected to fulfill its functions: "To frame is to select some aspects of a perceived reality and make them more salient in a communicating text, in such a way as to promote a particular problem definition, casual interpretation, moral evaluation, and/or treatment recommendation" (Entman, 1993, p. 52), which can be summarized as: define problems, diagnose causes, make moral judgments, and suggest remedies (Chu, 2010). McQuail (2005) pointed out the default of framing that since framing is involved in the interpretation process, it is likely inevitable for a journalist to "depart from pure 'objectivity' to introduce some (unintended) bias" (p. 379).…”
Section: Framing Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…News media has an intimate bond with framing, which is expected to fulfill its functions: "To frame is to select some aspects of a perceived reality and make them more salient in a communicating text, in such a way as to promote a particular problem definition, casual interpretation, moral evaluation, and/or treatment recommendation" (Entman, 1993, p. 52), which can be summarized as: define problems, diagnose causes, make moral judgments, and suggest remedies (Chu, 2010). McQuail (2005) pointed out the default of framing that since framing is involved in the interpretation process, it is likely inevitable for a journalist to "depart from pure 'objectivity' to introduce some (unintended) bias" (p. 379).…”
Section: Framing Theorymentioning
confidence: 99%
“…In regards to how U.S. media covered and framed China, Chang (2008) examined was examined (Chu, 2010). In terms of frames, sources, and tone, Chu (2010) found that the Mainland Chinese newspapers shed light on attribution of responsibility and morality frames with a positive stance, while Hong Kong newspapers emphasized the human interest and responsibility frames by presenting neutral side.…”
Section: Recent Framing Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The government regulates the news media through the General Administration of Press and Publication of the People's Republic of China. The agency has the right to issue or revoke news media licenses (CCEC.GOV, N.D.), establish press regulations and laws, and appoint or remove chief editors (Chu, 2010).…”
Section: Media System In Chinamentioning
confidence: 99%